Erythema Multiforme Major Associated With Community-Acquired Pneumonia: Lessons From a Case Report - Fan, Xiaomei; Luo, Yong; Lu, Jieluan; Xu, Jinji; Chen, Qing; Guo, Huijuan; Jin, Ping (Frontiers in Pediatrics, 2021)
Background: Erythema multiforme (EM) is an acute immune-mediated inflammatory mucinous skin disorder. The etiology of pediatric EM involves infections, medications, autoimmune diseases, and genetic factors. Case report: An 8-year-old girl with Mycoplasma pneumoniae (MP) associated community-acquired pneumonia developed erythema target-like symptoms one week after azithromycin administration. The erythema quickly spread throughout the body involving the oral and ocular mucous membranes, the trunk, and the extremities, and eventually developed into erythema multiform major (EMM). Through drug withdrawal and specific treatment including systemic corticosteroids and supportive care, her clinical symptoms were improved. After 31 days, most of the mucocutaneous symptoms were relieved, except pigmentation. Human leukocyte antigen (HLA) gene sequencing was performed and 20 HLA genotypes were identified. The patient follow-up lasted for 18 months. Rashes appeared on her trunk when receiving azithromycin orally after discharge and then disappeared after azithromycin withdrawal. Conclusions: Pediatric EM is a rare disease and recognition of its etiology is important for EM management. In this case, azithromycin and HLA-DQB1*03:01 genotype may contribute to EMM. Lesson: For drug-induced EM, rapid identification and withdrawal of the causative drugs is critical. Re-exposure to the same drug or exposure to drugs with similar chemical structures should also be avoided. Patient education and rational use of medicines are essential for pediatric patients.